Suplemento proteico e monensina para bovinos em pastejo no período das águas - Coutinho, Marina Pereira Souza (2021)
Two experiments with crossbred heifers (Nellore breed predominance) under grazing during the rainy season were carried out with the objective of evaluate the effect of monensin inclusion on protein and mineral supplements on productive performance, pasture consumption, dry matter intake and nutrient digestibility, as well as to identify changes in the ingestive behavior of heifers, thermal comfort and its relationship with ingestive behavior through the Index of thermal stress for cows (ITSC) in grazing. The experimental area consisted of 7 hectares of Brachiaria brizantha cv. Marandu under continuous stocking, located in Rondonópolis-MT. In both experiments, a 2x2 factorial scheme and a completely randomized design were adopted. The first experiment was carried out from December 2015 to March 2016. The treatments consisted of two protein supplements (high and low consumption) and the inclusion or not of monensin. Productive performance, nutrient consumption and digestibility were evaluated. Forty heifers with an average initial weight of 213.8 ± 4.5 kg were used. There was no difference (P>0.05) in the animals' performance among treatments, with an average daily gain of 0.588 kg animalday -1 . There was no interaction (P<0.05) between sodium monensin and supplements for consumption and digestibility variables, except for crude protein (CP) digestibility. There was equality in the dry matter (DM) intake among treatments (± 2% of the animals' body weight). However, there was a reduction (P<0.05) in pasture intake with the high consumption supplement, showing a substitutive effect. There was no treatments effect on the digestibility parameters (P> 0.05), but a greater CP digestibility (P<0.05) was observed when monensin was associated with low-consumption protein. It was concluded that monensin does not improve the performance of grazing heifers by consuming high and low consumption protein supplements, and its use is dispensable. The second experiment was carried out from December 2016 to March 2017. The treatments consisted of two supplements (mineral and protein) and the inclusion or not of monensin. Forty heifers with an average age and initial weight of 9 months and 159.2 ± 1.3 kg, respectively, were used. There was no interaction (P> 0.05) between the supplement type and monensin and there was no influence (P> 0.05) of the supplement type on the animals' performance. However, monensin promoted greater (P <0.05) weight gain of the animals (± 107 ganimal.day-1 ). There was an interaction (P <0.05) between supplementation and monensina inclusion on behavioral activities, except for idle time. There was equality in the average grazing time (455 minutes) of animals that received mineral supplement, regardless of the monensin inclusion. The monensin inclusion in the protein supplement reduced (P <0.05) the grazing time by 45 minutes. The ITSC value influenced (P <0.05) the ingestive behavior and the increase of this index reduced the grazing time in all treatments. Monensin improves the weight gain of animals grazing tropical forages under continuous stocking management.